Efficacy and Safety of Nonvitamin K Oral Anticoagulants in Patients with Atrial Fibrillation and Cancer: A Study-Level Meta-Analysis - Cavallari, Ilaria; Verolino, Giuseppe; Romano, Silvio; Patti, Giuseppe (Thrombosis and Haemostasis, 2020)
Objectives In this study-level meta-analysis, we evaluated the clinical outcome with nonvitamin K antagonist oral anticoagulants (NOACs) versus vitamin K antagonists (VKAs) in atrial fibrillation (AF) patients with cancer.Background Anticoagulation in AF patients with cancer is challenging given the coexistence of elevated thrombotic and bleeding risk. The efficacy and safety of NOACs in this setting remain unclear.Methods We included three randomized trials in our primary analysis (N = 2,661 patients) and three observational studies in our secondary, confirmatory analysis (N = 21,112 patients). Outcome measures were: the composite of any stroke or systemic embolism, ischemic stroke, venous thromboembolism, major bleeding, intracranial bleeding; and all-cause death. Mean follow-up duration was 2.2 years.Results In the primary analysis, the use of NOACs was associated with similar incidence of stroke/systemic embolism (odds ratio [OR] 0.70, 95% confidence interval 0.45–1.09; p = 0.11), ischemic stroke (OR 0.71, 0.31–1.64; p = 0.42), venous thromboembolism (OR 0.91, 0.33–2.53; p = 0.86), all-cause death (OR 1.02, 0.72–1.42; p = 0.93), and major bleeding (OR 0.81, 0.61–1.06; p = 0.13) compared with VKAs. The occurrence of intracranial bleeding was significantly lower in the NOACs versus VKAs group (OR 0.11, 0.02–0.63; p = 0.01). These results were overall confirmed in the secondary analysis, where there was additionally a significant reduction of stroke/systemic embolism, ischemic stroke, and venous thromboembolism with NOACs.Conclusion In AF patients with malignancy, NOACs appear at least as effective as VKAs in preventing thrombotic events and reduce intracranial bleeding. NOACs may represent a valid and more practical alternative to VKAs in this setting of high-risk patients.
Keywords: atrial fibrillation; cancer; anticoagulation; stroke; bleeding